A Bécsi Egyetem Szent László-orációi a 17. században - Farkas, Krisztina (Gerundium, 2019)
Saint Ladislaus’ Day Orations at the University of Vienna in the 17th Century. The University of Vienna played a highly important role in the promotion of Saint Ladislaus’ cult in the 16th century. The festive oration was presented on the occasion of the annual solemnities held in honour of St. Ladislaus by a specially chosen student. Due to the king’s presence and under the influence of Jesuit supervision actual political topics and analogies between Habsburg sovereigns and St. Ladislaus were highly appreciated in the text of orations. There are two sources of collected editions of St. Ladislaus day’s orations available for study. The first one is owed to Franciscus Xaverius Cetto who collected and published in 1693 orations presented after 1655. The second volume was produced by Miklós Jankovich at the end of the 18th century. The latter is the only source of Miklós Zrínyi’s first prose work (1634). He depicts St. Ladislaus as hero of knight king, predecissor of Ferdinand III. with the inclusion of first clues to Zrínyi’s future political programme. His thoughts are also reflected in the orations by counts Esterházy in which comparison to Habsburg monarchs gains even more emphasis. Similar parallelism appears on the portrait St. Ladislaus of the Nádasdy- Mausoleum which was inspired by the Augsburg and Brunn edition of the Thuróczy’s Chronicle (1488).